Problems of Contemporary Public Administration: Content Analysis of Scientific Publications - A. A. Likhtin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The purpose of this article is to characterize the current trends in public administration research in European countries. Methodologically, the article is based on the content analysis of the leading journals in the field of research of the theory and practice of public administration in European countries. The journals, which form the basis for the analysis of the subject area of the European science of public administration, are a theoretical and methodological platform in the field of public administration, which serves as a unifying framework for scientists and practitioners interested in the public sector and public sector management. Analysis of current trends and research provides a factual basis for decision-making, presents an accessible format, and encourages discussion. Journals on public administration in European countries are an institutional whole, not the least role in the stable significance of which is played by the «hypothesis — method» bundle, which does not allow writing and further publishing articles of a proveless nature. A total of 410 articles from six top journals (1–39 place (Q1) Scimago Journal & Country Rank) for 2017–2020 were analyzed. The analysis of articles shows that most of the journals are aimed at publishing articles of an analytical, methodological, and theoretical nature on five main topics: theoretical and methodological approaches to the study of public policy and public administration; national public political events and processes; the European Union as an actor in regional and international affairs; institutions, politics, and political processes in the European Union and other countries of the world; state policy of interaction between the European Union and other states, as well as comparative studies related to multidimensional issues of public administration. The practical result of the article is the formation of a pool of hypotheses for the study of public administration in conjunction with specific methods that allow these hypotheses to be tested. The reviewed articles reflect a steady interest among scientists and practitioners in understanding projects, the effectiveness of public policy instruments, and the organizational level factors that make it possible to implement them. They reveal how public policy embodies broader trends in society in terms of new regulatory approaches, initiatives, and mechanisms.